Islam, Budaya dan komunikasi antarbudaya Islam di Indonesia: Analisa Hubungan Agama-Negara Pasca Pembubaran HTI - rofiah siddiq (Prodi Ilmu Komunikasi Universitas Putera Batam, 2018)
The occurrence of contacts between various ethnic groups in Indonesia, the different respond to socio-political conditions in Indonesia, the occurrence of Indonesian Islamic affiliations with various countries, gave diverse Islamic cultures with various roles and functions in the history of Indonesia's development since colonial period. to the existence, role and function of various existing Islamic cultural identities, conflict of identity cannot be avoided. This condition requires an intercultural communication with the principle of mutual understanding, mutual respect and mutual support, as in the concept of intercultural communication by Ting-Toomey (1999). Government support for one of the Islamic cultures in Indonesia has triggered a conflict of triangles between the government, Islamic culture mainstreams and Islamic culture streams. With the constructivism paradigm, this study interpreted social facts constructed based on subjective experience of informants. Qualitative data and analysis were obtained from twenty informants as sources of research in B